J.H. Prynne's romanticism: Wordsworth and the dawn of neoliberalism. Issue 7 (3rd July 2021) - Stanley, Joshua
ABSTRACT: This essay is an account of J.H. Prynne's uses of and references to British romantic poetry in his poems of the 1960s and 1970s. Prynne used and thought through British romantic poetry, especially the poetry of Wordsworth, as a way of imagining alternative social relations to those of capitalism during these decades. Prynne's relationship to romanticism changes abruptly in the late 1970s when the accumulation of capital began to stabilise and the epoch of neoliberalism began. British romanticism at this point was becoming one part of a nationalist and racist symbolic imaginary proper to Thatcherism. Inextricably linked to this wish to imagine and create alternative social relations is a preoccupation with one of the central forms of romantic poetry: the mid-length irregular (Pindaric) ode, which predominates in Prynne's major collections of this period. In studying this aspect of Prynne's writing in relation to the 1960s and 1970s, this essay is concerned with what I would call historical materialist poetics. Historical poetics is the study of poems at the intersection of the history of techniques, the discourses of aesthetics and evolving modes of critical mediation; a historical materialist poetics would also understand these in terms of shifting relations of production.